A Model of Performance Evaluation for Healthcare Workers Based on Satisfaction and Remuneration (Financial and Non-Financial) - Wahyuhadi, Joni; Hidayah, Nur; Aini, Qurratul (Folia Medica Indonesiana, 2022)
Highlights: • This study aimed to formulate an evaluation model of the performance of health workers. • Employee performance targets and employee satisfaction were assessed by considering the financial and non-financial remuneration, Job Description Index (JDI), competencies, and motivation. • The performance evaluation model for health workers shows the importance of remuneration for government agencies, employees, and employee performance. Abstract: This study aimed to formulate an evaluation model of the performance of health workers from the perspective of financial and non-financial satisfaction and remuneration. The research method used was a literature study with a literature review approach. The research findings were the healthcare workers' performance evaluation model based on satisfaction and remuneration. The evaluation was conducted by assessing the employee performance targets (sasaran kerja pegawai/SKP) and employee satisfaction related to the financial and non-financial remuneration, Job Description Index (JDI), competencies, and motivation. In addition, this model has been also used for the evaluation of performance appraisal based on remuneration among employees (i.e. health workers) in government agencies, especially hospitals.